Machining of titanium alloy (Ti-6Al-4V) - theory to application - Pramanik, Alokesh; Littlefair, G. (Taylor & Francis, 2015)
This paper correlates laboratory based understanding in machining of titanium alloys with theindustry based outputs and find possible solutions to improve machining efficiency oftitanium alloy Ti-6Al-4V. The machining outputs are explained based on different aspects ofchip formation mechanism and practical issues faced by industries during titaniummachining. This study also analyzed and linked the methods that effectively improve themachinability of titanium alloys. It is found that the deformation mechanism duringmachining of titanium alloys is complex and causes basic challenges, such as saw-toothchips, high temperature, high stress on cutting tool, high tool wear and undercut parts. Thesechallenges are correlated and affected by each other. Saw tooth-chips cause variation incutting forces which results in high cyclic stress on cutting tools. On the other hand, lowthermal conductivity of titanium alloy causes high temperature. These cause a favorableenvironment for high tool wear. Thus, improvements in machining titanium alloy dependmainly on overcoming the complexities associated with the inherent properties of this alloy.Vibration analysis kit, high pressure coolant, cryogenic cooling, thermally enhancedmachining, hybrid machining and, use of high conductive cutting tool and tool holdersimprove the machinability of titanium alloy.